Blush-On Compact Powder dengan Pewarna Alami dari Ekstrak Etanol Kulit Buah Naga (Hylocereus Lemairei) - Ni Made Dharma Shantini Suena; Rr. Asih Juanita; Ni Putu Udayana Antari (Jurnal Penelitian Pendidikan IPA, 2023)
Cosmetics are one of the women's basic needs, but several cosmetic products on the market use synthetic dyes such as Rhodamine B, which cause various risks dangerous to health. Natural dyes are non-toxic, renewable, and environmentally friendly, one of which is anthocyanins found in dragon fruit peel. Blush-on is a cosmetic containing a dye that women often use. This study aimed to determine that the dragon fruit peel ethanolic extract can be used as a natural dye in blush-on compact powder preparations with good physical quality. Blush-on was made with various concentrations of dragon fruit peel ethanol extract of 20% (F1), 25% (F2), and 30% (F3). The preparations were observed for organoleptic and homogeneity, pH value, friability, and hedonic test during four weeks of storage, with descriptive data analysis. The results showed that dragon fruit peel extract blush-on did not meet some of the physical quality test requirements for blush-on. It is because the color of the blush-on should be red. However, the color of the preparation is white to brownish, and the preparation is also fragile. The preparation meets the requirements of homogeneity and pH value according to the physiological pH of the skin. It remains stable for four weeks of storage. F1 is the most preferred by panelists based on a preference test for the preparation's shape, color, and odor. Dragon fruit peel extract blush-on has not yet fulfilled its function as a decorative cosmetic to give color to the skin